RADIATION PROTECTION: AN INITIAL ASSESSMENT OF LEVEL OF KNOWLEDGE AND COMPLIANCE AMONGST RADIATION WORKERS IN AHMADU BELLO UNIVERSITY TEACHING HOSPITAL ZARIA, NIGERIA - Lawal S; Ibrahim MZ; Igashi JB; Muhammad HM; Bello N (Ntec Specialist, 2019)
Background: Medical use of ionizing radiation can result to deleterious effects such as undesirable somatic and genetic modifications, although less radiation dose is involved in diagnostic radiology. This necessitates the need for radiation safety practices, to bring to the barest minimum possibility of these risks. This study was aimed at assessing the knowledge and radiation safety practices amongst radiation workers in Ahmadu Bello University Teaching Hospital (ABUTH) Zaria, Nigeria. Method: The study was conducted amongst radiologist, radiology resident doctors, radiographers, nurses, and technicians, with the use of questionnaire for assessment of knowledge, attitude and covert monitoring of personnel for assessment of implementation. Data was analyzed with Statistical Package for Social Sciences (SPSS) for Windows® version 20. Results: Assessment of knowledge was quite impressive with average score 91% and 78% for the radiologists/residents and the radiographers respectively, while the group of "Others" (i.e. nurses and technician) was abysmal with a score 42%. Radiation protection gadgets were either lacking or obsolete. Application of shielding devices such as gonad shield for protection and thermoluminescent devices (TLDs) were neglected by about 56% of the personnel. The x-ray imaging machines were quite old with no quality assurance tests performed for quite some time. Conclusion: Excellent knowledge of radiation protection was exhibited by the majority of radiation workers in ABUTH, though from self-efforts. However, compliance with the standard radiation protection guidelines is appalling. The need for improved and sustained efforts by both the management and the personnel in radiation protection can never be over emphasized in order to avoid deleterious effects of radiation on both the personnel and patients.